Moral Pluralism in Behavioural Spillovers: A cross-disciplinary account of the multiple ways in which we engage in moral valuing - Michael Vincent; Ann-Kathrin Koessler (ZBW – Leibniz Information Centre for Economics, 2019)
In this article, we reflect critically on how moral actions are categorised in some recent studies on moral spillovers. Based on classic concepts from moral philosophy, we present a framework to categorise moral actions. We argue that with a finer classification of the moral values, associated behaviour is better understood, and this understanding helps to identify the conditions under which moral licensing takes place. We illustrate our argument with examples from the literature on pro-environmental behaviours. Moral spillovers are frequently studied in this behavioural domain and to understand what causes their occurrence is highly (policy) relevant if we wish to promote sustainable behaviour.
Keywords: 330; moral values; moral licensing; pro-environmental behavior; behavioral spillover; value pluralism